Mitigation of safety vulnerability of people and property from the effects of explosions of explosive materials in the Serbian Army / Смягчение угрозы безопасности населения и имущества от последствий взрыва взрывчатых средств в Вооруженных силах Республики Сербия / Ublažavanje bezbednosne ugroženosti ljudi i imovine od efekata eksplozije eksplozivnih sredstava u Vojsci Srbije - Dejan S. Stojanović (Vojnotehnički Glasnik, 2016)
The aim of the research is to provide proactive mitigation of safety risk to people and property of the effects of explosions of explosive materials in the Serbian Army based on a large number of relevant collected data. Achieving these research goals requires the use of appropriate methods and techniques for understanding and studying the existing theoretical and practical solutions as well as proposing new solutions in the area of interest. The research includes possibilities to mitigate risk to people and property from the effects of explosive material explosions. These possibilities aim at reducing danger, risk and threat to the population, their property and the environment, as well as at mitigating the consequences of possible emergencies. The following methods have also been discussed: avoidance, retention, reduction, division, transfer and reduction of hazards, risks and threats, where for each method a detailed theoretical explanation is provided with appropriate examples of good practice. The formulated hypothesis is also being proven, with the aim to - with a scientific objectivity towards one's own research results - accept or reject the proposed methods. / На основании данного исследования представлены возможности смягчения угрозы безопасности населения и имущества от взрыва взрывчатых средств. Исследование проведено с целью определения мер по снижению опасности, рисков и угроз длянаселения, имущества и окружающей среды и смягчения последствий чрезвычайных ситуаций. В статье также подробно описаны следующие методы: профилактика, отсрочивание, снижение, распределение, перенос и уменьшение опасности, рисков и угроз, подкрепленные соответствующими практическими примерами. В процессе исследования, автор стремился доказать гипотезу с объективностью научного подхода к результатам собственных трудово применении представленных методов. / Istraživanjem su obuhvaćene mogućnosti za ublažavanje bezbednosne ugroženosti ljudi i imovine od efekata eksplozije eksplozivnih sredstava koje imaju za cilj da smanje opasnost, rizik i pretnju po stanovništvo, njihovu imovinu i životnu sredinu, kao i da ublaže posledice moguće vanredne situacije. Razmotrene su sledeće metode: izbegavanje, zadržavanje, umanjenje, podela, prenos i redukcija opasnosti, rizika i pretnji. Svaka metoda je detaljno teorijski objašnjena, uz adekvatne primere iz prakse. Dokazivana je postavljena hipoteza koja ima za cilj da, prilazeći s naučnom objektivnošću vlastitim rezultatima istraživanja, prihvati ili odbaci predložene metode.